Health Disparities in Czechia and Portugal at Country and Municipality Levels - Lustigova, Michala (2019)
This article investigates the health outcomes and determinants between two different European populations, Portuguese and Czech, on two hierarchical levels: country and metropolitan area. At first, the decomposition method of age and cause of death were compared on the country level, and then health was examined based on a factor analysis at the municipality level of Prague and Lisbon. The results clearly indicate problematic diabetes mortality among the Portuguese population, and especially in the Lisbon Metropolitan Area, and confirm the dominant role of circulatory mortality and cancer mortality among Czech, especially the Prague population. The social and economic deprivations were revealed as the major drivers for both metropolitan areas, although with differences between them, requiring interventions that go beyond the health sector.